ALAT PENDETEKSI WARNA UNTUK PENDERITA BUTA WARNA MENGGUNAKAN SENSOR TCS34725 - Puteri Mas Agung, Tiara Nurlisda; Novriyanti, Dea; Sulistyo, Eko; Priestiani, Priestiani (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2025)
Color blindness is a condition that affects a person's ability to distinguish colors, which often interferes with daily activities. This research aims to create a color detection device that can help people with color blindness to accurately recognize the colors of objects around them. This tool uses the TCS34725 sensor, which is known for its ability to detect RGB colors, and the Arduino Mega Pro Mini as the data processing platform. In its implementation, it outputs a color signal or information through a speaker, allowing color-blind users to understand the detected colors. Tests were conducted under various lighting conditions to determine the accuracy of the tool. The results show that this tool is effective in helping people with color blindness identify basic colors, although there are limitations that need to be considered. The color detector designed using TCS34725 color sensor and Arduino Mega Pro Mini microcontroller has recognized various colors with sound output and is able to detect various colors such as red, green, blue, yellow, purple, and so on, with sufficient success in stable lighting conditions.